Study of kinetic and adsorption isotherm of ibuprofen on mcm-41 synthesized with rice husk - Olyvia Azzahra Putri Hartono; Frida Octavia Purnomo; Dyah Ayuwati Waluyo; Tunas Alam; Mohammad Jihad Madiabu (Universitas Ahmad Dahlan, 2024)
Rice husk is one of the abundant wastes, especially in agricultural countries. Rice husk waste has a silica content of 95.80%, where the silica content can be utilized to make an adsorbent. One of the adsorbents that can be made is Mobil Composition of Matter 41 (MCM-41), a material with a hexagonal structure with a surface area to adsorb ibuprofen. Based on the results of the research that has been done, MCM-41 synthesized with rice husk has the same characterization results as MCM-41 synthesized with commercial materials tetraethyl orthosilicate (TEOS). Fourier Transform Infrared Spectroscopy (FTIR) characterization results show the absorption peak is at wave number 1068.58 cm1 which shows asymmetric Si-O-Si stretching vibrations and at 799.60 cm-1 region is symmetric Si-OSi stretching vibrations. X-ray diffraction (XRD) characterization results show an hexagonal crystal form at 2θ = 20o -30o . Scanning Electron Microscope (SEM) characterization results show particle of 2,664 μm. Based on the results of the research that has been done MCM-41 synthesized from rice husk can adsorb ibuprofen with Langmuir isotherm approach and Pseudo Second Order kinetics, and the maximum adsorbing capacity is 34.48 mg/g.